Orienting of attention - Wright, Richard D., 1956- (Oxford University Press, 2008)
This book is a succinct introduction to the orienting of attention. Richard Wright and Lawrence Ward describe the covert orienting literature clearly and concisely, illustrating it with numerous high-quality images, specifically designed to make the challenging theoretical concepts very accessible. The book begins with an historical introduction that provides a great deal of information about orienting, much of which will be new even to seasoned researchers. Wright and Ward then systematically describe the development of various experimental paradigms that have been devised to study covert ori.